A self-assembled DNA tetrahedron as a carrier for in vivo liver-specific delivery of siRNA - Kim, Kyoung-Ran; Jegal, Hyun; Kim, Junghyun; Ahn, Dae-Ro (ROYAL SOC CHEMISTRY, 2020)
While siRNA is a potent therapeutic tool that can silence disease-causing mRNA, its in vivo potency can be compromised due to the lack of target tissue specificity. Here, we report a wireframe tetrahedral DNA nanostructure having a 20-mer duplex on each side that can be specifically distributed into the liver upon systemic administration. This liver-targeted DNA tetrahedron is employed as the carrier for liver-specific delivery of siRNA targeting ApoB1 mRNA, which is overexpressed in hypercholesterolemia. When delivered by a DNA tetrahedron, the siRNA can preferentially be accumulated in the liver and down-regulate the ApoB1 protein. As a result, the blood cholesterol level is also decreased by the siRNA. These results successfully demonstrate that the DNA tetrahedron is a promising carrier for liver-targeted delivery of therapeutic nucleic acids.
Keywords: DRUG-DELIVERY; NANOSTRUCTURES; NANOPARTICLES; DESIGN; SYSTEM; GENE